The labor of luck : casino capitalism in the United States and South Africa - Sallaz, Jeffrey J., 1974- (University of California Press, 2009)
In this gripping ethnography, Jeffrey J. Sallaz goes behind the scenes of the global casino industry to investigate the radically different worlds of work and leisure he found in identically designed casinos in the United States and South Africa. Seamlessly weaving political and economic history with his own personal experience, Sallaz provides a riveting account of two years spent working among both countries' casino dealers, pit bosses, and politicians. While the popular imagination sees the Nevada casino as a hedonistic world of consumption, The Labor of Luck shows that the "Vegas experienc.